FACTORS INFLUENCING DEPRESSION AMONG LATE ADOLESCENTS AFTER THE COVID-19 PANDEMIC: A CROSS-SECTIONAL STUDY IN KLAENG DISTRICT, RAYONG, THAILAND - วรรณศรี , กุลกมล; วัฒนสินธุ์, ดวงใจ; เฮงอุดมทรัพย์ , ภรภัทร (Primary Health Care Journal (Northeastern Edition), 2025)
Depression is a prevalent mental health issue among late adolescents in the post-COVID-19 era, driven by the necessity for adaptation and significant lifestyle changes. Understanding the factors associated with depression is crucial for developing effective prevention strategies. This cross-sectional descriptive study aimed to investigate depression and its influencing factors among late adolescents in Klaeng District, Rayong Province. A sample of 166 participants was selected using stratified random sampling. Data collection was conducted via questionnaires between August and September 2022. Data were analyzed using descriptive statistics and stepwise multiple regression analysis. The results revealed that 63.86% of late adolescents experienced depression, classified as mild to moderate (22.29%) and severe (41.57%). Factors significantly influencing depression included resilience (β = -0.49, 95% CI [-0.610, -0.370]), pandemic fatigue (β = 0.27, 95% CI [0.149, 0.391]), and cyberbullying (β = 0.15, 95% CI [0.026, 0.274]). Together, these factors accounted for 39.50% of the variance in depression (R2 = 0.395, F = 35.72, p < 0.001). These findings indicate a relatively high prevalence of depression among late adolescents following the COVID-19 pandemic. Resilience served as a protective psychological factor, whereas pandemic fatigue and cyberbullying were identified as significant risk factors associated with depression. Therefore, healthcare professionals overseeing the mental health of this demographic should implement regular depression screening. Furthermore, interventions aimed at promoting resilience, mitigating pandemic fatigue, and reducing cyberbullying should be prioritized to effectively prevent depression in late adolescents.